Design of Residence Hall for Electricity Conservation - Balbarona, Juvy; Manegdeg, Ferdinand; Guevarra, Shirley (Philippine Engineering Journal; Vol 40 No 1 (2019), 2019)
Abstract – The reduction of electricity consumption of residence halls in a university without compromising the level of comfortability and nurturing environment and or increasing the level of comfortability and nurturing environment at optimal electricity consumption are the goals of efficient and sustainable university residence hall administration. This paper presents the results of the study for all the residence halls in the University of the Philippines Diliman campus. The established framework for determining the energy intensity of residence halls is used to determine factors that contribute to the current level of electricity consumption. Using Pareto analysis, ventilation is identified as the most energy intensive process contributing to 37% of the total monthly electricity consumption of all the residence halls, followed by lighting at 25% and then computing at 24%. The average electricity consumption per resident is 46.9 kWh per month with a standard deviation of 10.6 kWh per month. Another two surveys were conducted to determine the preferences of the residents in terms of the design of residence hall rooms and common areas, and on different categories describing residence hall characteristics. Some of the results from the respondents are: 52% chose rooms with both task and accent lighting to comply with user’s requirements; 62% chose a balance between comfort and efficiency with personal closets, desks and storages; and 43% chose two residents per room with an area of 25 m 2 . Sample residence hall room designs as well as energy consumption models for two different scenarios are presented. Air conditioned room is more expensive by 2.5 times compared to electric fan ventilated room. It is recommended to identify the effects of different residence hall architectural features in the academic performance of residents; to develop design protocols incorporating the survey results; and to develop the level of comfortability that the university is willing to subsidize.   Keywords—Residence Hall Energy Consumption, Academic Dormitory Energy Intensity, Building Energy Conservation